1993
DOI: 10.3109/01485019308988370
|View full text |Cite
|
Sign up to set email alerts
|

Hyperviscosity and Hypofunction of the Seminal Vesicles

Abstract: The study was designed to determine whether hyperviscosity of the semen sample is related to dysfunction of the male accessory glands. It was carried out on men who consecutively attended an infertility clinic between June 1989 and June 1991, and the men were grouped according to viscosity of semen samples (normal viscosity or higher viscosity). Semen samples from 229 infertility patients were studied. From these, 155 had normal viscosity and 74 showed hyperviscosity. The effect of hyperviscosity of semen samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 15 publications
3
33
1
Order By: Relevance
“…This prevalence was considerably lower than that found by Gonzales et al [8,9], but considerably higher when compared with that found by Gopalkrishnan et al [27] WBCs and/or inflammatory alterations observed by ultrasound. Group C, subjects negative for the above situations.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…This prevalence was considerably lower than that found by Gonzales et al [8,9], but considerably higher when compared with that found by Gopalkrishnan et al [27] WBCs and/or inflammatory alterations observed by ultrasound. Group C, subjects negative for the above situations.…”
Section: Discussioncontrasting
confidence: 51%
“…Gonzales et al [8,9] and Andrade-Rocha [10] showed reduced levels of fructose in SHV, and hypothesized inadequate functioning of the seminal vesicles as the explanation. Carpino and Siciliano [11] studied the possible correlation between SHV and protein secretion of the epididymis, vesicles and prostate.…”
Section: Introductionmentioning
confidence: 99%
“…Semen samples coagulation and liquefaction with their physiological characteristics are still not fully understood; however, the negative effects of hyperviscosity on semen parameters, above all motility, are known. As reported in literature, hyperviscosity is due to a "trapping effect" that prevents normal sperm progression through the female genital tract (9,(10)(11)(12). There is evidence of a correlation between hyperviscosity (SHV) and low levels of fructose in seminal plasma, due to an impaired function of the seminal vesicles (11).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we found that seminal hyperviscosity was related to hypofunction of the seminal vesicles [6] and suggested that the effect on male fertility is more than a simple mechanical effect.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, semen with high amounts of seminal-vesicular fluid had low-chromatin zinc and low stability of sperm chromatin [2]. Since seminal hyperviscosity is associated with low vesicular fluid and a relatively high "prostatic fluid" [6], then stability of sperm chromatin should be increased.…”
Section: G F Gonzales and A Stinchezmentioning
confidence: 99%